Reservoir rainfall‐runoff geomorphological model. II: analysis, calibration and validation. Issue 4 (23rd May 2012) - Goñi, M.; López, J. J.; Gimena, F. N.
Abstract The model presented in the complementary document entitled, Reservoir rainfall‐runoff geomorphological model I: parameter application and analysis is analysed, calibrated and validated in this paper. The accuracy of simulated hydrographs is analysed by means of the efficiency defined by Nash and Sutcliffe. The sensitivity of the influence of five parameters on the behaviour of the model developed is analysed. Two different calibration and validation processes of Reservoir rainfall‐runoff geomorphological model are performed in Aixola watershed. Twelve events have been selected for calibrations and 25 for validations. With the first calibration and validation process, the model parameters are set by assigning the medians' values of the distributions obtained by means of the optimum results. The second process is performed by calibrating the most determinant parameter in the adjustment, which is the one that indicates the proportion of infiltrated water that is retained and does not flow; this is done with an empirical formulation depending on the event characteristics. Subsequently, the obtained results are validated. This last process has achieved very good adjustments in both calibrated and validated events. Copyright © 2012 John Wiley & Sons, Ltd.